Ride-hailing versus traditional taxi services: The experiences of taxi drivers in Lebanon - Jad Yassin; Uma Rani (International Labour Organization (ILO), 2022)
Lebanon is experiencing a structural transformation of its economy and labour market, but at the same time has been hit by a series of crises in recent years. In the face of rising unemployment, it is often argued that digital platforms can offer new employment and income-generating opportunities. The platform economy's role in structural change is not yet clear, but digital labour platforms undoubtedly have significant growth potential. An important concern is whether digital platforms can provide not merely jobs but decent jobs that could help to dampen the effects of rampant unemployment in Lebanon. This paper provides insights into the working conditions of platform-based taxi drivers, examining, among other aspects, the question of flexibility and autonomy at work and algorithmic management practices. It engages critically with the trajectory and development of taxi platforms and shows how they depend heavily on venture capital funds, the "non-uberized" economy, the State and the non-market society in Lebanon. The paper also identifies areas in which regulations are required to harness the potential of digital platforms and other technological innovations to generate decent work opportunities.
Keywords: 330; decent work; future of work; informal employment; digital labour; conditions of employment; work organization; trade unions; social security; gig economy